The Impact of Real Rents and Wages on Household Formation - Haurin, Donald R.; Hendershott, Patric H.; Kim, Dongwook (The Review of Economics and Statistics, 1993)
Although the economic literature has analyzed some components of the headship decision, study of household formation has been primarily in the realm of demography. The authors expand the demographic model to include economic determinants of the decision to remain with parents or not and to live with a group or separately. They focus on measuring the effect of spatial variations in rental costs on the probability of forming a household. The authors' results, based on a sample of 2, 573 youths in their twenties, indicate that the cost of housing and potential labor earnings are important variables in explaining this probability. Copyright 1993 by MIT Press.